Spectrum on non-surgical causes of internal jugular vein thrombosis in otorhinolaryngology practice - Mohamed, Mohd Hazmi; Ishak, Azlan Iskandar; Wan Sulaiman, Wan Aliaa (Universiti Putra Malaysia Press, 2023)
Internal jugular vein thrombosis is an uncommon entity secondary to various aetiologies. In the pre-antibiotic era, it was commonly associated with Lemierre syndrome, a septic thrombophlebitis of the internal jugular vein secondary to oropharyngeal infection. With the advent of antibiotics, Lemierre syndrome has become a rare entity and is often overlooked. Internal jugular vein thrombosis may also occur in the setting of malignancy, a combination referred to as Trousseau's syndrome, which is not well documented.